ROS-generation potential of Humic-like substances (HULIS) in ambient PM2.5 in urban Shanghai: Association with HULIS concentration and light absorbance. (October 2020) - Xu, Xiaoya; Lu, Xiaohui; Li, Xiang; Liu, Yaxi; Wang, Xiaofei; Chen, Hong; Chen, Jianmin; Yang, Xin; Fu, Tzung-May; Zhao, Qianbiao; Fu, Qingyan
Abstract: Ambient fine particulate matter (PM2.5 ) can cause adverse health effects through the generation of reactive oxygen species (ROS) after inhalation. Humic-like substances (HULIS) are major constituents contributing to the ROS-generation potential in organic aerosols. In this study, PM2.5 samples in urban Shanghai during autumn and winter (2018–2019) were collected. Mass-normalized ·OH generation rate in surrogate lung fluid (SLF) was used to denote the intrinsic ROS-generation potential of PM2.5 or of the HULIS isolated from PM2.5 . In this study, ROS-generation potential of PM2.5 decreased with increasing ambient PM2.5 concentration due to higher percentage of inorganic components in high PM2.5 event. Same trend was observed for the ROS-generation potential of unit mass of HULIS, which was higher when HULIS and PM2.5 concentrations were both relatively lower. The HULIS with high ROS-generation potential but low concentration (High-ROS/Low-Conc HULIS) were likely produced by the atmospheric aqueous-phase reactions during nighttime or under high relative humidity conditions, not from biomass burning emissions or the photochemical pollution products. The association between ROS-generation potential and light absorption properties of HULIS was studied as well. The High-ROS/Low-Conc HULIS also showed stronger light absorbance than the other HULIS. Our results implied the potentially important roles that HULIS species might play in atmospheric environment and human health even when the PM2.5 pollution is low. Highlights: HULIS with high ROS-generation potential were observed at low PM2.5 concentration. High-ROS/Low-Conc HULIS were likely formed via aqueous-phase reactions. HULIS with higher ROS-generation potential showed stronger light absorbance.